Fields of blood : religion and the history of violence - Armstrong, Karen, 1944- (New York : Alfred A. Knopf, 2014)
'From the renowned and best-selling author of A History of God, a sweeping exploration of religion's connection to violence. For the first time in American history, religious self-identification is on the decline. Some have cited a perception that began to grow after Sept 11: That faith in general is a source of aggression, intolerance and divisiveness--something bad for society. But how accurate is that view? And does it apply equally to all faiths? In these troubled times, we risk basing decisions of real and dangerous consequence on mistaken understandings of the faiths subscribed around us, in our immediate community as well as globally. And so, with her deep learning and sympathetic understanding, Karen Armstrong examines the impulse toward violence in each of the world's great religions.
Includes bibliographical references (pages 405-488) and index.
Keywords: Violence -- Religious aspects